Conocimientos y prácticas de prevención de tuberculosis pulmonar en los usuarios del Centro de Salud de Miraflores de la ciudad de Loja - Armijos Medina, Nathali Carolina (2019)
The pulmonary tuberculosis is the second cause of death in the world, and the first cause of infectious diseases. The tuberculosis is a bacterial contagious disease, it affects mainly the lungs. In spite of the approach of the Ministery of health has been imposible to eradicate this disease, and for this reason is necesary to present this investigation. “Knowledge and practices of prevention of pulmonay tuberculosis in the users of medical center from Miraflores in Loja city”. was a descriptive and cross investigation. for the data collection it was used two poll, the first for to determine knowledge and the second for identify prevention practices, these were applied a 250 users. The results was that; less than half of people are female population in ages of 36-50 years, the 27,2% are singles, the 34,4% have secondary studies. In knowledge more than 80% unknown the definition, classification, signs and symptons, ways of contagion, risk factors and exposed groups. In prevetions practices it was determined that more than 50 %, apply; hand washing, and respiratory protection, Conversely approximately 60% have not been administered the BCG vaccine, don't adequate spaces and ventilation, and don’t maintains a healthy diet. For this reason it concludes that the knowledge and practices used are not adequate to prevent contagion and prevent disease. Key Words: prevention, signs and symptons, treatment, BCG vaccine.